Controls on the Spatial Distribution of Near‐Surface Pyrogenic Carbon on Hillslopes 1 Year Following Wildfire. Issue 6 (15th June 2021) - McGuire, Luke A.; Rasmussen, Craig; Youberg, Ann M.; Sanderman, Jonathan; Fenerty, Brendan
Abstract: Wildfire alters hydrologic and geomorphic systems, promoting increases in runoff and erosion relative to unburned areas. As a result, pyrogenic carbon (PyC) produced by wildfires can experience substantial lateral redistribution from overland flow. Since landscape position helps to determine the fate of PyC, it is critical to understand the geomorphic factors that govern its lateral redistribution as well as the sensitivity of those factors to soil burn severity, which controls the magnitude of many wildfire‐induced hydrologic and geomorphic changes. In this study, we quantified the spatial distribution of near‐surface (0–5 cm) PyC on three hillslopes roughly 1 year after the 2018 Buzzard Fire in the Gila National Forest, New Mexico, USA. We then use hydrologic monitoring data, terrain analysis, and rainfall‐runoff modeling to explain the observed spatial distribution of PyC. Near‐surface PyC concentrations decreased from averages of roughly 12–8 g/kg as slope and unit stream power increased by factors of ∼2 and 4, respectively, on a hillslope burned at low severity. This suggests that susceptibility to runoff‐driven erosion was a dominant control on the redistribution of PyC. In contrast, the spatial distribution of PyC in areas burned at moderate to high severity was independent of slope and unit stream power. We attribute this pattern to intense runoff and lack of canopy cover, which promoted erosion of PyC regardless of slope and landscape position. Results demonstrate that how wildfire‐induced hydrogeomorphic changes can modulate the importance of terrain attributes in controlling the spatial distribution of PyC in upland landscapes. Key Points: Soil burn severity impacted relationships between the spatial distribution of pyrogenic carbon (PyC) on hillslopes and hydrogeomorphic variables Near‐surface PyC on a low burn severity hillslope is best correlated with topographic slope following 1 year of erosion Near‐surface PyC on moderate/high burn severity hillslopes is not correlated with slope or unit stream power after 1 year of erosion